Training primary care physicians to offer their patients faecal occult blood testing and colonoscopy for colorectal cancer screening on an equal basis: a pilot intervention with before–after and parallel group surveys. Issue 5 (13th May 2016) - Selby, Kevin; Cornuz, Jacques; Gachoud, David; Bulliard, Jean-Luc; Nichita, Cristina; Dorta, Gian; Ducros, Cyril; Auer, Reto
Abstract : Objectives: Primary care physicians (PCPs) should prescribe faecal immunochemical testing (FIT) or colonoscopy for colorectal cancer screening based on their patient's values and preferences. However, there are wide variations between PCPs in the screening method prescribed. The objective was to assess the impact of an educational intervention on PCPs' intent to offer FIT or colonoscopy on an equal basis. Design: Survey before and after training seminars, with a parallel comparison through a mailed survey to PCPs not attending the training seminars. Setting: All PCPs in the canton of Vaud, Switzerland. Participants: Of 592 eligible PCPs, 133 (22%) attended a seminar and 106 (80%) filled both surveys. 109 (24%) PCPs who did not attend the seminars returned the mailed survey. Intervention: A 2 h-long interactive seminar targeting PCP knowledge, skills and attitudes regarding offering a choice of colorectal cancer (CRC) screening options. Outcome measures: The primary outcome was PCP intention of having their patients screened with FIT and colonoscopy in equal proportions (between 40% and 60% each). Secondary outcomes were the perceived role of PCPs in screening decisions (from paternalistic to informed decision-making) and correct answer to a clinical vignette. Results: Before the seminars, 8% of PCPs reported that they had equal proportions of their patients screened for CRC by FIT and colonoscopy; after the seminar, 33% foresaw having their patients screened in equal proportions (p<0.001). Among those not attending, there was no change (13% vs 14%, p=0.8). Of those attending, there was no change in their perceived role in screening decisions, while the proportion responding correctly to a clinical vignette increased (88–99%, p<0.001). Conclusions: An interactive training seminar increased the proportion of physicians with the intention to prescribe FIT and colonoscopy in equal proportions.